2011
DOI: 10.1021/es201153k
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Contaminant Removal of Reverse Osmosis and Advanced Oxidation in Full-Scale Operation by Combining Passive Sampling with Chemical Analysis and Bioanalytical Tools

Abstract: Advanced water treatment of secondary treated effluent requires stringent quality control to achieve a water quality suitable for augmenting drinking water supplies. The removal of micropollutants such as pesticides, industrial chemicals, endocrine disrupting chemicals (EDC), pharmaceuticals, and personal care products (PPCP) is paramount. As the concentrations of individual contaminants are typically low, frequent analytical screening is both laborious and costly. We propose and validate an approach for conti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
44
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 67 publications
(47 citation statements)
references
References 32 publications
(56 reference statements)
3
44
0
Order By: Relevance
“…Thus the majority of NDMA exposure for humans is not from drinking water consumption and the increased risk to human health from NDMA provided by drinking water consumption is still relatively minor. Our assessment of a low health risk from ROtreated WW agrees with other assessments undertaken using multiple bioassays (Van Buynder et al 2009;Escher et al 2011;Macova et al 2011). In particular, screening undertaken during the project using a cytokinesis-block micronucleus assay with a human lymphoblastoid cell-line indicated that there was no significant cytotoxicity or genotoxicity for either secondary wastewater or RO-treated wastewater (Van Buynder et al 2009), and the toxicity of RO-treated WW has been shown to be indistinguishable from that of drinking water .…”
Section: Screening Health Risk Assessment Of Ro Permeatesupporting
confidence: 89%
“…Thus the majority of NDMA exposure for humans is not from drinking water consumption and the increased risk to human health from NDMA provided by drinking water consumption is still relatively minor. Our assessment of a low health risk from ROtreated WW agrees with other assessments undertaken using multiple bioassays (Van Buynder et al 2009;Escher et al 2011;Macova et al 2011). In particular, screening undertaken during the project using a cytokinesis-block micronucleus assay with a human lymphoblastoid cell-line indicated that there was no significant cytotoxicity or genotoxicity for either secondary wastewater or RO-treated wastewater (Van Buynder et al 2009), and the toxicity of RO-treated WW has been shown to be indistinguishable from that of drinking water .…”
Section: Screening Health Risk Assessment Of Ro Permeatesupporting
confidence: 89%
“…A similar approach for the oxidative stress response quantified with the AREc32 bioassay resulted in a provisional EBT-EC IR1.5 of 3 REF . Both provisional EBT-EC were able to suitably differentiate between water quality before and after advanced water treatment in recycling In contrast to integrative assays, the majority of receptormediated effects (e.g., inhibition of enzymes or activation of hormone receptors) can typically be explained by known chemicals (Escher et al, 2011;Leusch et al, 2005Leusch et al, , 2014bRutishauser et al, 2004;Tang and Escher, 2014). Effects can be expressed as socalled bioanalytical equivalent concentrations (BEQ), which represent the concentrations of a reference chemical that would elicit the same effect as the water sample of unknown composition.…”
Section: Need For Effect-based Trigger Values (Ebt)mentioning
confidence: 99%
“…Time-weighted average concentrations (c TWA ) of pesticides in the water phase were calculated from a generic sampling rate for all target compounds (Escher et al, 2011) Chemcatchers were the sampling devices of choice for this study because they reliably detect polar and semi-polar pesticides in surface waters (Schäfer et al, 2008a(Schäfer et al, , 2008bShaw et al, 2010;Stephens et al, 2005). An SDB-RPS Empore disk modified with sulfonic acid groups was applied as receiving phase to detect hydrophilic and semi-hydrophilic chemicals with log K OW b 4 (Gunold et al, 2008;Moschet et al, 2015;Sanchez-Bayo and Hyne, 2014;Stephens et al, 2005;Vermeirssen et al, 2008).…”
Section: Pesticide Measurementsmentioning
confidence: 99%
“…For the calculation of c TWA , we propose the use of a generic sampling rate (as suggested by Escher et al (2011) in another context), additionally corrected for specific hydrodynamic conditions at each sampling site, which would make the use of Chemcatchers even easier.…”
Section: Ordermentioning
confidence: 99%